Desenvolvimento de método voltamétrico de determinação de benzo(a)pireno em amostras de água de abastecimento e cachaça - Sales, Flávia Rhuana Pereira (2020)
Among polycyclic aromatic hydrocarbons, benzo(a)pyrene (BaP) is one of the best known and studied, due to evidence of carcinogenicity in humans and animals. Produced from incomplete combustion of organic matter, they can be found in several matrices, for example, cachaça. BaP can be determined by several analytical techniques, including voltammetric techniques. In this sense, the electrochemical oxidation of BaP was investigated at different pH values and concentration times, as well as the use of surfactants and the volume quantity of water-acetonitrile in electrochemistry employing carbon paste electrode (CPE), using the voltammetric method of determination in supply water and distilled drink. With the study of the aforementioned parameters, an experimental condition was obtained - 1: 1 mixture of Britton-Robinson (BR) pH 4.0 buffer and acetonitrile, pre-concentration time of 10 minutes in open circuit potential and 10 mg L-1 of the sodium dodecyl sulfate surfactant - where a well-defined oxidation peak at +1.06 V (vs. Ag / AgCl) was observed by square wave voltammetry (VOQ) with EPC in 100 g L -1 of BaP. The CPE was modified with gold nanoparticles synthesized by electrodeposition. The CPE modification showed greater sensitivity and was chosen for the development of the method. In order to obtain more reproducible answers, a factorial design for robust optimization, Taguchi method, was used to select the ideal levels of the studied parameters. Once the electrode and voltammetric conditions of analysis were established, the method presented a linear working range from 20 g L-1 to 260 g L-1 , reaching the detection limit (LD) 0.29 g L-1 ( 1.14 nmol L-1 ) and limit of quantification (LQ) of 0.96 g L-1 (3.8 nmol L-1 ). The method was applied to determine BaP in samples of drinking water and cachaça and the results were compared to those obtained with fluorescence spectroscopy using the paired t student statistical method, showing good agreement between the two techniques. The LD and LQ of the developed method are close to those obtained in the literature by the classical electrochemical methods.